ANALISIS REGIONAL EXPENDITURE DI KOTA DAN KABUPATEN YANG ADA DI KALIMANTAN BARAT - Asteria, Beta; Riauwanto, Selamat (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study analyzed the factors that affect Regional Expenditures in Cities and Regencies in West Kalimantan. This study used a panel data which is a combination of time series and cross section data, while the overall data sample is 56. Data analysis was carried out using multiple linear regression. The results of the study proved that Regional Original Income (PAD) has a negative and significant effect on Regional Expenditures, because the sig value on the PAD variable is 0.000 less than alpha=0.05. General Allocation Fund (DAU) has a positive and significant effect on Regional Expenditures. Based on the results of data processing, the sig value on the DAU variable is 0.000 less than α=0.05. Special Allocation Fund (DAK) has a positive and significant effect on Regional Expenditures. Based on the results of data processing, the sig value for the DAK variable is 0.041less than alpha=0.05. Local Revenues (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) simultaneously have a significant effect on Regional Expenditures based on the results of data processing in this study obtained a sig value of 0.000 less than α=0.05. Based on the Coefficient of Determination Test (R2), the value of Adj R2 is 0.653 or 65.30 percent, meaning that the variability of Regional Expenditures can be explained by the variables of Regional Original Income (PAD), General Allocation Funds (DAU) and Special Allocation Funds (DAK) of 65.30 percent whereas 34.70 percent is explained by other variables outside the research model.